2024
DOI: 10.1002/marc.202400103
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Polysarcosine‐Containing Nanoparticles by Ring‐Opening Polymerization‐Induced Self‐Assembly

Anna H. Morrell,
Nicholas J. Warren,
Paul D. Thornton

Abstract: N‐carboxyanhydride ring‐opening polymerisation‐induced self‐assembly (NCA ROPISA) offers a convenient route for generating poly(amino acid)‐based nanoparticles in a single step, crucially avoiding the need for post‐polymerisation self‐assembly. Most examples of NCA ROPISA make use of a poly(ethylene glycol) hydrophilic stabilising block, however this non‐biodegradable, oil‐derived, polymer and may cause an immunological response in some individuals. Alternative water‐soluble polymers are therefore highly sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…The hydrophobic PBLG or PZLL blocks are assumed to form the core while interacting through their secondary structures, for example, helix–helix or β-sheet interactions (Figure B–D). Specifically the formation of anisotropic and elongated nanoparticles from amphiphilic block copolymers containing PBLG has been reported in previous studies in agreement with the structures observed here. ,, It is usually ascribed to antiparallel helix–helix alignment.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The hydrophobic PBLG or PZLL blocks are assumed to form the core while interacting through their secondary structures, for example, helix–helix or β-sheet interactions (Figure B–D). Specifically the formation of anisotropic and elongated nanoparticles from amphiphilic block copolymers containing PBLG has been reported in previous studies in agreement with the structures observed here. ,, It is usually ascribed to antiparallel helix–helix alignment.…”
supporting
confidence: 92%
“…More desirable are nanostructures fully derived from amino acids for reasons of biocompatibility and degradability and as simplistic biomimetic models of natural proteins. Very recently Thornton et al and Bonduelle et al independently reported aqueous ROPISA using poly(sarcosine) and polyLPro as hydrophilic blocks. , In both cases, nanostructures were obtained in a two-step process initiating NCA chain extension from preformed macroinitiators using Schlenk line and glovebox procedures. The challenge for a fully NCA ROPISA process lies in the fact that all proteogenic amino acid NCAs are hydrophobic, if not intrinsically, then through side chain protection, while a successful PISA process relies on in situ generation of amphiphilicity.…”
mentioning
confidence: 99%